PENATALAKSANAAN FISIOTERAPI PADA KASUS OSTEOARTHRITIS GENU DEXTRA DENGAN MODALITAS MICROWAVE DIATHERMY DAN TERAPI LATIHAN - Tasha Christabella P N; Ika Rahman (LPPM STIKES Siti Hajar dan Insight Power, 2021)
Osteoarthritis (OA) is a long-term chronic disease characterized by the deterioration of joint cartilage which causes bones to rub against each other and triggers stiffness, pain, and impaired daily movement.Objective: This study aims to determine the implementation of physiotherapy in reducing pain, increasing muscle strength, and increasing the functional ability of the knee muscles in patients with Osteoarthritis Genu Dextra with Microwave Diathermy and Exercise Therapy as the modalities. Results: After doing therapy 6 times, the results of the assessment of pain reduction in the right knee were obtained, namely tenderness in the right knee, namely T1 = 2 to T6 = 1, and motion pain in the right knee T1 = 4 to T6 = 1. Increased muscle value in the right knee, namely in flexion movements, T1 = 3+ to T6 = 5 and extension movements, T1 = 4 to T6 = 5. Increased functional activity abilities with the Jette scale experienced changes in standing from a sitting position, pain in T1 =3 becomes T6 =1; Difficulty T1=1 becomes T6, dependence T1=2 becomes T6=1. Then when walking, pain at T1 = 3 becomes T6 = 1 , Difficulty T1 = 3 becomes T6 = 2 , dependence on T1 = 1 becomes T6 = 1 , and up and downstairs, pain at T1 = 3 becomes T6 = 1; Difficulty T1=3 becomes T6 dependency T1= 2 becomes T6 =1. Conclusion: The use of Microwave Diathermy and Exercise Therapy can help reduce pain, increase muscle strength and improve the functional ability of the knee muscles in the case of Osteoarthritis Genu Dextra.Keywords: Osteoarthritis, Microwave Diathermy, Exercise TherapyOsteoarthritis (OA) adalah penyakit kronis jangka panjang yang ditandai dengan kemunduran tulang rawan sendi yang menyebabkan tulang saling bergesekan dan memicu timbulnya kekakuan, nyeri, dan gangguan gerakan sehari-hari.Tujuan Untuk mengetahui pelaksanaan Fisioterapi dalam menurunkan nyeri, meningkatkan kekuatan otot dan meningkatkan kemampuan fungsional otot lutut pada penderita Osteoarthritis Genu Dextra dengan modalitas Microwave Diathermy dan Terapi Latihan. Hasil : Setelah dilakukan terapi sebanyak 6 kali didapat hasil penilaian penurunan nyeri pada lutut kanan , yaitu nyeri tekan pada lutut kanan yaitu T1= 2 menjadi T6 =1, dan nyeri gerak pada lutut kanan T1= 4 menjadi T6 =1. Peningkatan nilai otot pada lutut kanan, yaitu pada gerakan fleksi, T1= 3+ menjadi T6 = 5 dan gerakan ekstensi, T1 = 4 menjadi T6 = 5. Peningkatan kemampuan aktivitas fungsional dengan skala jette mengalami perubahan pada berdiri dari posisi duduk, nyeri pada T1=3 menjadi T6 =1; Kesulitan T1=1 menjadi T6, ketergantungan T1= 2 menjadi T6 =1. Lalu saat jalan , nyeri pada T1=3 menjadi T6 =1 , Kesulitan T1=3 menjadi T6 = 2 , ketergantungan T1= 1 menjadi T6 =1 , dan Naik turun tangga, nyeri pada T1=3 menjadi T6 =1; Kesulitan T1=3 menjadi T6 ketergantungan T1= 2 menjadi T6 =1. Kesimpulan : Penggunaan Microwave Diathermy dan Terapi Latihan dapat membantu menurunkan nyeri, meningkatkan kekuatan otot dan meningkatkan kemampuan fungsional otot lutut pada kasus Osteoarthritis Genu Dextra.Kata Kunci: Osteoarthritis, Microwave Diathermy, Terapi Latihan